2002
DOI: 10.21236/ada399819
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Performance Resulting from the Design of Selected Hand-Held Input Control Devices and Visual Displays

Abstract: Since the introduction of graphical user interfaces (GUIs), input control devices have become an integral part of desktop computing. When interfacing with GUIs, these input control devices have become the human's primary means of communicating with the computer. Although there have been a number experiments conducted on pointing devices for desktop machine, there is little research on pointing devices for wearable computer technology. This is surprising because pointing devices are a major component of a weara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…If differences were significant, the D-C gain setting that produced the fewest errors was chosen as the optimum gain setting. Otherwise, the D-C gain setting that produced the fastest task completion time was selected (consistent with procedures used in Spencer, 2000). If different D-C gain level produced fastest speed and fewest errors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If differences were significant, the D-C gain setting that produced the fewest errors was chosen as the optimum gain setting. Otherwise, the D-C gain setting that produced the fastest task completion time was selected (consistent with procedures used in Spencer, 2000). If different D-C gain level produced fastest speed and fewest errors.…”
Section: Discussionmentioning
confidence: 99%
“…Indirect control input devices can be used with a helmet mounted display (HMD) or a wrist-mounted display (WMD), however direct input control devices can only be used with WMDs. Since an HMD will be used in the proposed research, only indirect control devices will be included (Spencer, 2000).…”
Section: Wearable Input Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…If differences were significant, the D-C gain setting that produced the fewest errors was chosen as the optimum gain setting. Otherwise, the D-C gain setting that produced the fastest task completion time was selected (consistent with procedures used in Spencer, 2000). D-C gain setting optimum for that device.…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Kanceler & Schopper (1993) determined that a combination of pointing and alphanumeric-capable devices provided the best increase in performance when spatial and text input tasks were performed. Finally, a study by Spencer (2002) found that pointing devices with rotational characteristics (e.g., a trackball) are optimal for target acquisition tasks. Each of these studies indicates that the use of alternative input devices can increase efficiency, but this effect is often task-specific.…”
Section: Introductionmentioning
confidence: 99%